Comparison of anaesthetic regime in patients undergoing third molar extraction. (13th September 2017) - McCarthy, C.; Warren, E.; Sleeman, D.
Abstract: Aims: Part 1: To determine whether intra‐operative local infiltration with lidocaine improves patient satisfaction following third molar extraction and the effect if any, its use has on the magnitude of acute pain. Part 2: To determine if bupivacaine has a prolonged effect on the period of acute post‐operative pain when compared to lidocaine. To analyse patient's preference in terms of local anaesthetic choice. Materials and methods: This two part, double blind, randomised, interventional clinical trial included 120 patients in total. All patients had symmetrically impacted lower third molars removed under general anaesthetic. Part 1 of the study involved 52 patients who received local anaesthetic in the form of 2% lidocaine with 1: 80, 000 epinepherine on one randomly allocated side. Pain was measured at 0, 30 and 60 min post‐surgery using a visual analogue scale (VAS). Part 2 enrolled 68 patients who received plain 0.5% bupivacaine on one randomly allocated side, with 2% lidocaine with 1: 80, 000 epinepherine administered on the opposite side. Pain was measured at 0, 30, 60 min (phase 1) and 3, 4, 6 and 8 h (phase 2) post‐surgery. Both studies involved psychological evaluations and patient reported outcomes, including patient satisfaction. Results: The difference in mean pain scores was statistically significant ( P < 0.001) for part 1 of this study. A significant difference ( P <0.05) was seen during phase 2 in part 2 of this study. Conclusions: Local anaesthetic is effective in reducing post‐surgical pain. Longer lasting anaesthetics such as bupivacaine can offer a longer period of analgesia, and improve overall patient satisfaction.